PELAKSANAAN PELATIHAN PROGRAM KESELAMATAN DAN KESEHATAN KERJA (K3) SEBAGAI UPAYA PENCEGAHAN KECELAKAAN KEJA PADA PT. SUPRACO INDONESIA DI DURI - Stefan, Ody Andika; ", Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Basically the strength that exists in a company lies in the people who are in the company. Lack of awareness of the importance of occupational safety and health is a benchmark in the implementation of work safety and health training programs.The purpose of this study was to determine the implementation of the Occupational Safety and Health Training Program (K3) as an Accident Prevention Effort at PT. Suoraco Indonesian in Duri.The theory concept that researchers use is Occupational Safety and Health (K3). This K3 program uses qualitative methods by analyzing data descriptively. In collecting data, researchers use interview, observation, and literature study techniques as sources of information.The implementation of K3 encountered several obstacles, namely the behavior of employees who violated the regulations set by the company, the culture of using PPE was often ignored by employees. In addition there is an assumption that using PPE only makes it difficult for employees when working, especially for those who are required to wear a complete PPE. Efforts made by the company in overcoming these obstacles are by providing safety induction, training and coaching, re-training, counseling, giving oral and written warnings, and direct supervision by QHSE management.Keywords : Training, Occupational Safety and Health